DEVELOPMENT OF MALANG LOCAL TEACHER INFLUENCE BASED ON ADOBE FLASH CS3 MEDIA ON BASIC STUDENTS OF INCLUSION TO INCREASE LEARNING OUTCOMES: TEACHING MATERIALS OF LOCAL MALANG - Cholifah, Tety Nur; Zuhroh, Luthfiatus (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This research is motivated by the low use of Malang Local Wisdom Teaching Materials based on Adobe Flash CS3 Media on Inclusive Elementary School Students because each teacher teaches with conventional methods, and the lack of students' knowledge about local wisdom around the area of residence. The objectives are (1) producing interesting teaching materials and (2) testing the effectiveness of teaching materials based on Malang local wisdom in inclusive elementary schools. This research is an R&D research that adapted the development model of Borg & Gall (1983). The research design is twofold namely preliminary field trials and main field trials with the subject of elementary school students' inclusion grades IV in the academic year 2018/2019 in Malang Regency. Data collection techniques using interview techniques, questionnaires, and tests. Data analysis in this research is qualitative and quantitative analysis. The results of this study Malang Local Wisdom Teaching Materials based on Adobe Flash CS3 Media on Inclusive Elementary School Students, this will provide an excellent interest for students so that students' insights and learning outcomes increase. This is supported by the results of assessments in the field trials of the main cognitive aspects with an average of 53,5 for pre-test and an average of 91,5 for post-test. Affective aspects on average for pre-test 2,125 "Not Good" category and 3,57 post-test "Very Good" category. The psychomotor aspect has an average of 3,75 "Very Good" categories.